The impact of structural changes on corporate real estate ownership: evidence from Germany - Seger, Julian; Pfnür, Andreas (International Journal of Strategic Property Management, 2021)
Although real estate resources represent a high percentage of the corporate assets of non-property companies, their future role is unclear. Longevity and difficulty in revising property-related decisions clash under dynamically changing environmental conditions. This makes it necessary to consider the ownership strategy and its altering role in order to avoid inefficiencies and not to hinder companies in mastering structural change successfully. In a first step, data from a telephone company survey (CATI) among 69 corporate real estate managers of German companies are grouped by performing a two-step cluster analysis according to the degree to which they are affected by structural change. The resulting clusters are then tested regarding differences in their ownership strategy. The empirical analysis shows that firms highly affected by structural change exhibit a higher willingness to decrease the proportion of ownership. The decline in real estate assets is particularly evident in the office segment and in increased acceptance of sale-and-rent-back solutions. First hints show that structural change and associated new business requirements change the relevance of CRE ownership. To avoid competitive disadvantages, especially European firms should scrutinize their high ownership ratios. First published online 09 November 2020